Reverse Sweep Opportunity in Facing Bad Pressure Early Marriage Based on Society 5.0 and Industry 4.0 - Bagas, Bagas Arri Atmaja; Ramadani, Febiola Djangkaru (IDFoS Indonesia, 2024)
This research entitled